About the Reaction to Styles of Thought on the Continental Drift Debate - Pellegrini, Pablo Ariel (2022)
The article appearing previously in this journal entitled “Styles of Thought on the Continental Drift Debate” (Pellegrini 2019) prompted a response from Weber and Šešelja (2020) which they termed as “a defence of rationalist accounts”. They argue that their self-designated “sophisticated rationalism” explains the closure of the continental-drift debate without being affected by my critiques to rationalist approaches. While ignoring the empirical evidence that shows the complexity of the debate and the necessity to include broader social elements in the analysis (such as scientists denying continental drift even after the plate tectonics theory, others supporting it without being familiarized with the literature), they proclaim to be unconvinced about the analysis of the styles of thought. In order to clarify differences in the approach to the continental-drift historical controversy, I respond here to the criticism my paper drew while discussing the place of rationalism when explaining the acceptance of a theory. I will argue that their distinction between “crude” and “sophisticated” rationalism does not solve the problem of social aspects being left aside by rationalists in view of the acceptance of a theory. I will also argue that in order to understand what leads people to embrace a belief (namely scientists in accepting a theory), the analysis of mere cognitive or epistemic arguments is not enough and it leads to a reductionist explanation as to social behaviour.